The Role of Ex-Migrant Worker Enterprise Toward Local Economic Development and Factors that Influence Income of Ex-Migrant Enterprise in Sumatera Utara Province - Supriana, Tavi; Nasution, Vita Lestari (Makara Human Behavior Studies in Asia, 2010)
The objective of research are: to analyze the role of the small scale enterprise of the ex-migrant workers towards the development of job opportunities and the empowerment of local economy as well as to analyze several factors that influence ex-migrant workers enterprise income. The research was carried out in North Sumatera Province. The descriptive analysis and the multiple linear regression analysis are used to analyze the data. The result of the research shows the small scale enterprise of the ex-migrant workers have important role for creating job opportunities. With assumption - every ex-migrant workers run a business and recruit minimum one worker - so the unemployment decrease as many as 123.226 people or 20,53% of the total unemployment in North Sumatera. The ex-migrant workers also have a role in the empowerment of the people economy. They work in the micro, small, medium enterprise which is the pillar of the national economy. The result of the research also shows that capital and the number of workers employed influence the income of ex-migrant enterprise. The addition capital of Rp1,000,000,00 will raise as much as Rp201,000.00 of income, and the addition of 1 worker will raise income as much as Rp44,757.562. Education, technical supporting and advance supporting done by government did not influence the income of ex-migrant enterprise. The implication is, government need to initiate the new model of technical supporting and advance supporting for exmigrant enterprise.